A SEQUENTIAL MODEL OF INNOVATION STRATEGYâCOMPANY NON-FINANCIAL PERFORMANCE LINKS - Ciptono, Wakhid Slamet (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
This study extends the prior research (Zahra and Das 1993) by examining the association between a companyâs innovation strategy and its non-financial performance in the upstream and downstream strategic business units (SBUs) of oil and gas companies. The sequential model suggests a causal sequence among six dimensions of innovation strategy (leadership orientation, process innovation, product/service innovation, external innovation source, internal innovation source, and investment) that may lead to higher company non-financial performance (productivity and operational reliability). The study distributed a questionnaire (by mail, e-mailed web system, and focus group discussion) to three levels of managers (top, middle, and first-line) of 49 oil and gas companies with 140 SBUs in Indonesia. These qualified samples fell into 47 upstream (supply-chain) companies with 132 SBUs, and 2 downstream (demand-chain) companies with 8 SBUs. A total of 1,332 individual usable questionnaires were returned thus qualified for analysis, representing an effective response rate of 50.19 percent. The researcher conducts structural equation modeling (SEM) and hierarchical multiple regression analysis to assess the goodness-of-fit between the research models and the sample data and to test whether innovation strategy mediates the impact of leadership orientation on company non-financial performance. SEM reveals that the models have met goodness-of-fit criteria, thus the interpretation of the sequential models fits with the data. The results of SEM and hierarchical multiple regression: (1) support the importance of innovation strategy as a determinant of company non-financial performance, (2) suggest that the sequential model is appropriate for examining the relationships between six dimensions of innovation strategy and company non-financial performance, and (3) show that the sequential model provides additional insights into the indirect contribution of the individual dimensions of innovation strategy (partially mediators) to company non-financial performance âproductivity or operational reliability. The findings provide empirical evidence extending the previous model of Zahra and Das. These findings also provide a basis for useful recommendations to upstream and downstream SBU managers attempting to implement a sequential model of innovation strategy âcompany non-financial performance links. This study shows that upstream SBUs rely on external innovation sources. They will acquire innovation policies through business partnership development (such as Joint Operation Body for Enhanced Oil Recovery or JOB-EOR, Joint Operation Body for Production Sharing Contract or JOB-PSC); licensing agreements (Technical Assistance Contract or TAC, Consortium Cooperation System); or acquisition with other firms (Joint Operating Contract or JOC). In contrast, downstream SBUs emphasize on generating internal innovation sources to develop their own in-house R&D efforts. The downstream SBUs should make extensive policies of internal innovation sources in their attempts to control the distribution of oil-based fuel and transmission of natural gas for domestic and international markets effectively. Both policies would enhance understanding and ultimately contribute to the improvement of company financial performance âsales, net profit margin, return on assets.